A high-safety polymer electrolyte and a preparation method thereof

CN122889834APending Publication Date: 2026-10-09ZHEJIANG ZHIYUAN NAKE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611374246.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

(1)传统无负极钠离子电池电解液一般采用醚基电解液体系,其稳定性极差,醚类小分子在金属钠沉积界面极易发生还原分解反应,持续消耗电芯内部有限的金属钠源;高温环境下电解液快速分解产气,造成电芯鼓包、界面持续劣化,长期高温循环容量衰减严重;同时液态电解液无阻燃功能,电芯发生针刺、微短路时极易剧烈放热、起火爆炸,热安全隐患突出

Benefits of technology

(1)本申请提供了一种高安全性聚合物电解质,以硅氧烷改性氨基甲酸酯单体为核心交联组分,搭配环状醚单体原位共聚构建耐还原三维柔性网络,复配专用钠盐、醚类增塑剂、复合引发剂,并引入氟代环磷腈阻燃添加剂;依靠硅氧烷分子骨架、氨基甲酸酯配位结构、丙烯酸酯交联位点与磷腈阻燃成膜组分协同增效,同步改善基体机械强度、耐钠还原稳定性、电极界面结合力与热阻燃能力,从交联骨架、负极 SEI 膜、高温副反应抑制、热失控防护、枝晶阻隔多维度解决传统电解质高温循环衰减快、高温存储容量跳水、钠枝晶易诱发微短路、针刺/热失控安全隐患突出等缺陷,适配无负极钠电池有限钠源、宽温域储能、高安全储能场景严苛工况。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889834A_ABST
    Figure CN122889834A_ABST
Patent Text Reader

Abstract

The application discloses a high-safety polymer electrolyte and a preparation method thereof, and belongs to the technical field of sodium ion batteries and electrolytes, and comprises a sodium salt, a flame-retardant additive and a copolymer, wherein the flame-retardant additive is a fluorinated cyclic phosphazene flame-retardant additive, and the copolymer is formed by cross-linking copolymerization of a siloxane-modified urethane monomer and a cyclic ether monomer; the high-safety polymer electrolyte is constructed by cross-linking copolymerization of the siloxane-modified urethane monomer and the cyclic ether monomer to form a flexible reduction-resistant three-dimensional cross-linking network, and is compounded with a specific fluorinated cyclic phosphazene flame-retardant component, so that the high-temperature stability, the flame-retardant safety and the wide-temperature-range cycle performance of the electrolyte are simultaneously strengthened; the application of the high-safety polymer electrolyte to a negative-electrode-free sodium ion battery can inhibit the risks of gas production, bulging and thermal runaway of the battery under heating, and significantly improves the safety performance of the negative-electrode-free sodium ion battery under high-temperature storage, overcharging and micro-short-circuit working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of sodium-ion battery and electrolyte technology, and particularly relates to a high-safety polymer electrolyte for negative electrode-free sodium-ion batteries and its preparation method. Background Technology

[0002] Electrodeless sodium-ion batteries, by abandoning traditional negative electrode active materials and using only current collectors as the sodium metal deposition substrate, have significant advantages in terms of lower cost and higher energy density. However, the electrolyte / electrolyte of electrodeless sodium-ion batteries currently suffers from the following technical defects that need to be addressed: (1) Traditional non-negative electrode sodium-ion battery electrolytes generally use ether-based electrolyte systems, which have extremely poor stability. Ether molecules are prone to reduction and decomposition reactions at the sodium metal deposition interface, continuously consuming the limited sodium metal source inside the cell. Under high temperature conditions, the electrolyte decomposes rapidly to produce gas, causing cell bulging, continuous interface deterioration, and severe capacity decay during long-term high-temperature cycling. At the same time, liquid electrolytes have no flame retardant function, and the cell is prone to violent heat release, fire and explosion when it is punctured or micro-short-circuited, resulting in prominent thermal safety hazards.

[0003] (2) Existing non-negative electrode sodium-ion batteries use ordinary cross-linked polymer electrolytes. The cross-linked network has high overall rigidity and cannot buffer the huge volume deformation caused by the deposition / stripping of metallic sodium. The generated SEI film is brittle and repeatedly cracks and regenerates during charging and discharging, continuously consuming active sodium. At the same time, it is very easy to induce sodium dendrite growth, resulting in dead sodium and local micro-short circuits. Conventional cross-linked systems lack urethane coordination structures, resulting in low sodium salt dissociation efficiency, a lack of ion transport channels, and a significant decline in rate and cycle performance.

[0004] Most existing polymer electrolyte systems do not contain dedicated flame retardant components and rely solely on the polymer skeleton to slightly improve thermal stability. They cannot capture combustion free radicals at high temperatures and are unable to suppress thermal runaway chain reactions. Even if a few systems introduce flame retardant additives, they cannot simultaneously achieve the dual effects of negative electrode interface passivation and flame retardancy. High-temperature storage and high-temperature cycling degradation problems remain significant.

[0005] Therefore, since there is no additional metallic sodium to compensate for irreversible losses in the sodium-ion battery system without a negative electrode, extremely high requirements are placed on the electrolyte's ability to resist sodium reduction, interface regulation, high temperature stability, and flame retardant safety performance. Existing technical solutions are difficult to simultaneously meet the requirements of long cycle life, high temperature storage stability, high temperature cycling performance, and needle penetration and thermal runaway safety protection. Summary of the Invention

[0006] The first objective of this application is to provide a high-safety polymer electrolyte that can significantly improve the high-temperature stability, flame-retardant safety, and wide-temperature-range cycling performance of the electrolyte in a negative electrode-free sodium battery.

[0007] To achieve the above-mentioned objectives, this application adopts the following technical solution: A high-safety polymer electrolyte includes a sodium salt, a flame retardant additive, and a copolymer, wherein the flame retardant additive is a fluorocyclophosphonitrile flame retardant additive, and the copolymer is formed by cross-linking and copolymerizing a siloxane-modified urethane monomer and a cyclic ether monomer.

[0008] This application discloses a high-safety polymer electrolyte that uses siloxane-modified urethane monomers and cyclic ether monomers to cross-polymerize and construct a flexible, reduction-resistant three-dimensional cross-linked network, and is compounded with specific fluorinated cyclophosphinitrogen flame-retardant components to simultaneously enhance the electrolyte's high-temperature stability, flame-retardant safety, and wide-temperature-range cycling performance.

[0009] The second objective of this application is to provide a method for preparing the aforementioned high-safety polymer electrolyte, comprising the following steps: (1) Preparation of polymer precursor liquid Sodium salt, plasticizer, fluorocyclophosphonitrile flame retardant additive, initiator, siloxane-modified urethane monomer, and cyclic ether monomer are mixed to prepare a polymer precursor liquid. (2) Preparation of high-safety polymer electrolytes The polymer precursor liquid is polymerized in situ at 40-90°C for 1-24 hours to obtain a high-safety polymer electrolyte.

[0010] Further settings include: In step (1): The sodium salt is at least one of NaPF6, NaClO4, NaBF4, NaBOB, NaODFB, NaCF3SO3, Na(CF3SO2)3, Na(CF3CO2)2N, Na(CF3SO2)2N, Na(SO2C2F5)2N, and Na(SO3CF3)2N.

[0011] The sodium salt has a mass fraction of 12%-25% based on the total mass of the polymer precursor liquid.

[0012] The plasticizer is selected from at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, acetonitrile, fluoroacetonitrile, isobutyronitrile, fluorobenzene, anisole, and methoxycyclopentane.

[0013] Based on the total mass of the polymer precursor liquid, the mass fraction of the plasticizer is 20%-70%, preferably 40%-60%.

[0014] The fluorocyclophosphonitrile flame retardant additive is selected from at least one of diethoxytetrafluorocyclotriphosphonitrile, ethoxy-phenoxytetrafluorocyclotriphosphonitrile, dimethoxytetrafluorocyclotriphosphonitrile, bistrifluoroethoxytetrafluorocyclotriphosphonitrile, ethoxypentafluorocyclotriphosphonitrile, methoxypentafluorocyclotriphosphonitrile, propoxypentafluorocyclotriphosphonitrile, isopropoxypentafluorocyclotriphosphonitrile, butoxypentafluorocyclotriphosphonitrile, trifluoroethoxypentafluorocyclotriphosphonitrile, phenoxypentafluorocyclotriphosphonitrile, trimethylsiloxypentafluorocyclotriphosphonitrile, hexaethoxycyclotriphosphonitrile, hexaphenoxycyclotriphosphonitrile, and triethoxytrifluorocyclotriphosphonitrile.

[0015] Based on the total mass of the polymer precursor liquid, the mass fraction of the fluorocyclophosphonitrile flame retardant additive is 0.5%-10%, preferably 1%-5%.

[0016] The initiator is selected from any one or a combination of at least two of the following: azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, aluminum tri(trifluorosulfonic acid), aluminum bis(fluorosulfonyl)imide, tin trifluorosulfonate, magnesium bis(trifluoromethylsulfonyl)imide, indium trifluorosulfonate, magnesium hexafluoroantimonate, tri(pentafluorophenyl)borane, and zinc tetrafluoroborate.

[0017] The initiator has a mass fraction of 0.01%-5% based on the total mass of the polymer precursor liquid.

[0018] The cyclic ether monomer is selected from at least one of 1,3-dioxolane, 1,3,5-trioxane, tetrahydrofuran, oxetane, 3-methyloxetane, 3-ethyloxetane, 1,4-dioxane monovinyl ether, and tetrahydrofuran-3-vinyl ether.

[0019] Based on the total mass of the polymer precursor liquid, the mass fraction of the cyclic ether monomer is 10%-50%, preferably 20%-40%.

[0020] The structural formula of the siloxane-modified carbamate monomer is as follows: ; Where: n≥1; Based on the total mass of the polymer precursor liquid, the mass fraction of the siloxane-modified urethane monomer is 1%-25%, preferably 1%-10%.

[0021] In step (2): The polymerization temperature is 55-65℃, and the polymerization time is 2-12h, with a particularly preferred polymerization time of 12h at 60℃.

[0022] The mechanism of action of this application is as follows: This application formulates a precursor solution by combining siloxane-modified urethane monomers, cyclic ether monomers, fluorocyclophosphonitrile additives, sodium salts, plasticizers, and initiators. This precursor solution is then polymerized in situ at 40–90°C to form a highly safe polymer electrolyte, simultaneously optimizing the battery's wide-temperature cycling performance and high-temperature safety. Its mechanism of action is as follows: (1) A reduction-resistant crosslinking backbone was constructed using siloxane-modified urethane monomers. The core siloxane-modified urethane monomer of this application has a trimethoxysilylpropylsiloxane end group, a middle urethane linking chain, and a terminal acrylate active alkoxyalkyl group. The flexible siloxane segments endow the crosslinked network with excellent resistance to sodium reduction and mechanical toughness. The urethane structure can promote sodium salt dissociation and build a continuous sodium ion transport channel. The terminal acrylate double bond can undergo ring-opening copolymerization with the cyclic ether monomer to form a dense crosslinked skeleton that runs through the battery cell. This siloxane hybrid structure can stabilize the interface between the electrolyte and the carbon-coated aluminum current collector, generate a highly elastic and crack-resistant organic-inorganic solid electrolyte interface film in situ, significantly inhibit the continuous reduction and decomposition of ether small molecules at the sodium deposition interface, reduce the irreversible loss of limited active sodium in the anode-free system, and improve the high-temperature cycling capacity retention rate.

[0023] (2) Adding fluorocyclophosphonitrile flame retardant additives achieves the dual effects of high-temperature film formation and flame retardancy. The polymer precursor liquid system of this application introduces a specific fluorinated cyclophosphinitrogen flame retardant additive. On the one hand, it can preferentially decompose on the surface of the negative electrode current collector to generate a dense passivation film rich in sodium fluoride, further blocking the contact between plasticizers, cyclic ether molecules and fresh metallic sodium at high temperatures, significantly reducing the rate of side reactions at high-temperature interfaces, and alleviating the problem of rapid capacity decay during long-term cycling at 60°C. On the other hand, the cyclic phosphinitrogen core has free radical capture and flame retardant effects, which can terminate the electrolyte combustion chain reaction at high temperatures, suppress the risk of cell heating and gas generation, bulging, and thermal runaway, and significantly improve the safety performance of the negative electrode cell under high-temperature storage, overcharging, and micro-short circuit conditions.

[0024] (3) Adding cyclic ether monomers to copolymerize reduces the content of free small molecules. In this application, cyclic ether monomers are introduced into the polymer precursor liquid system. After the various cyclic ethers are opened, they are covalently fixed to the polymer backbone, reducing the continuous decomposition of free ethers at high temperatures and the consumption of sodium source. Sodium ions are coordinated at the oxygen sites of the ethers within the molecule, and a continuous ionic pathway is constructed in conjunction with the plasticizer, taking into account both crosslinking strength and ionic conductivity.

[0025] The third aspect of this application is to provide a negative electrode-free sodium-ion battery, including a positive electrode, a separator, a polymer electrolyte, and a negative electrode current collector, wherein the separator is disposed between the positive electrode and the negative electrode current collector, and the polymer electrolyte is formed by in-situ polymerization of a polymer precursor liquid.

[0026] The active material of the positive electrode is selected from any one of sodium-based layered metal oxides, iron-based polyanionic compounds, Prussian blue compounds, and iron sulfides.

[0027] The diaphragm is selected from one of the following: polypropylene diaphragm, polyethylene diaphragm, inorganic ceramic coated diaphragm, and alumina ceramic modified PP / PE composite diaphragm.

[0028] The negative electrode current collector is made of at least one of copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil, porous copper foil, and porous aluminum foil.

[0029] Compared with existing technical solutions, this application has the following advantages: (1) This application provides a high-safety polymer electrolyte, which uses siloxane-modified urethane monomer as the core crosslinking component, and combines it with cyclic ether monomer in situ copolymerization to construct a reduction-resistant three-dimensional flexible network. It is compounded with special sodium salt, ether plasticizer, composite initiator, and introduces fluorinated cyclophosphonitrile flame retardant additive. Relying on the synergistic effect of siloxane molecular skeleton, urethane coordination structure, acrylate crosslinking site and phosphonitrile flame retardant film-forming component, it simultaneously improves the matrix mechanical strength, sodium reduction resistance stability, electrode interface bonding force and thermal flame retardancy. It solves the defects of traditional electrolytes such as fast high-temperature cycle decay, high-temperature storage capacity drop, sodium dendrite easy to induce micro short circuit, and prominent needle puncture / thermal runaway safety hazards from multiple dimensions such as crosslinking skeleton, negative electrode SEI film, high temperature side reaction suppression, thermal runaway protection and dendrite barrier. It is suitable for the harsh working conditions of sodium-free batteries with limited sodium source, wide temperature range energy storage and high safety energy storage scenarios.

[0030] (2) The negative electrode-free sodium-ion battery prepared using the polymer electrolyte of this application has significantly superior overall performance and safety performance compared to existing systems: Excellent long-cycle performance at room temperature: After 1000 cycles at 25℃ and 0.5C charge / 1C discharge, the capacity retention rate reaches over 92%, with no irreversible capacity accumulation or capacity cliff decay issues. Its long-cycle stability is superior to that of ordinary polyether and polyurethane cross-linked electrolytes.

[0031] High-temperature cycling stability is significantly improved: after 300 cycles at 60℃ and 0.5C / 1C, the capacity retention rate can reach more than 85%; the thermal decomposition temperature of the siloxane cross-linked network is significantly improved, the cyclic ether is covalently fixed in the skeleton to reduce free small molecules, and a NaF-rich stable SEI film is constructed with fluorinated cyclophosphinitrogen, which inhibits the continuous reduction and consumption of active sodium by the solvent at high temperature. The high-temperature decay rate is much lower than that of the comparative system without siloxane and phosphinitrogen flame retardant additives.

[0032] Outstanding stability under long-term high-temperature conditions: After being stored at 60℃ for 28 days, the capacity retention rate exceeds 92%; the cross-linked network binds the liquid solvent, and the phosphazene additive continuously inhibits the high-temperature interface side reactions, avoiding continuous decomposition and gas generation and cell bulging, which greatly improves the reliability of high-temperature static storage.

[0033] Outstanding thermal runaway and needle penetration protection capabilities: Under adiabatic accelerated calorimetry testing, the thermal runaway trigger temperature of the battery cell is significantly increased, and the peak temperature rise rate is significantly reduced; the needle penetration test shows no fire, explosion, or continuous heat release, with only a small temperature rise, completely solving the safety pain point of thermal runaway and fire after needle penetration of traditional liquid electrolytes and ordinary polymer electrolytes.

[0034] The polymer electrolyte of this application utilizes a synergistic effect of siloxane and urethane to form a highly tough hybrid SEI film on the surface of a carbon-coated aluminum current collector, uniformly dispersing surface charges. A dense three-dimensional cross-linked network physically suppresses sodium dendrite growth, reducing dead sodium accumulation and the risk of localized micro-short circuits, thereby lowering the probability of short circuits triggering thermal runaway within the battery cell from the source. Fluorocyclophosphinitrogen can capture combustion free radicals, terminating the high-temperature oxidation chain reaction in the electrolyte.

[0035] (3) This application adopts in-situ polymerization process, which has strong industrial adaptability: after the polymer precursor liquid is directly injected into the battery cell, it is cross-linked and copolymerized at 40-90℃, without the need for independent film making and bonding processes. It is compatible with high-capacity cathode and carbon-coated aluminum current collector mass production lines, and the industrialization cost is low. Attached Figure Description

[0036] Figure 1 The infrared spectrum of the copolymer prepared in Example 1 and 1,3-dioxolane.

[0037] Figure 2 The ¹H NMR spectra of the monomers in Example 1 before and after polymerization are shown. Detailed Implementation

[0038] The technical solutions of this application will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of this application, and should not be construed as limiting the scope of protection of this application. All technologies implemented based on the above content of this application are covered within the scope of protection intended by this application.

[0039] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0040] Example 1

[0041] A method for preparing a highly safe polymer electrolyte includes the following steps: (1) Preparation of polymer precursor liquid The polymer precursor liquid contains sodium salt, plasticizer, fluorocyclophosphonitrile flame retardant additive, initiator, and polymerization monomer, which consists of cyclic ether monomer and siloxane-modified urethane monomer.

[0042] Sodium salt: Sodium hexafluorophosphate (NaPF6).

[0043] Plasticizer: Diethylene glycol dimethyl ether.

[0044] Fluorinated cyclophosphonitrile flame retardant additive: diethoxytetrafluorocyclotriphosphonitrile.

[0045] Initiator: Azobisisobutyronitrile (AIBN).

[0046] Siloxane-modified urethane monomer: Trimethoxysilylpropylacrylate ethoxyurethane, with the following structural formula: ; Cyclic ether monomer: 1,3-dioxolane.

[0047] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 51.5% diethylene glycol dimethyl ether, 3% diethoxytetrafluorocyclotriphosphazene, 0.5% AIBN, 3% diethoxytetrafluorocyclotriphosphazene, 2% trimethoxysilylpropyl acrylate ethoxycarbamate, and 25% 1,3-dioxolane.

[0048] Preparation method of polymer precursor liquid: In a high-purity argon glove box with water and oxygen content <10ppm, the fully dried sodium salt is completely dissolved in the mixture of plasticizer and polymer monomer. After stirring evenly, the initiator is added and stirring is continued for 3 hours to obtain a uniform and transparent polymer precursor liquid.

[0049] (2) Preparation of high-safety polymer electrolytes The polymer precursor liquid prepared above was in situ polymerized by holding it at 60°C for 12 h to obtain a high-safety polymer electrolyte.

[0050] Product characterization: The structural formula of the copolymer obtained by in-situ polymerization of polymer precursor liquid is as follows: ;

[0051] In the formula: n≥500.

[0052] The prepared copolymer was subjected to infrared spectroscopy and nuclear magnetic resonance tests to verify that the cyclic ether monomer and the siloxane-modified urethane monomer crosslinked and copolymerized, and successfully prepared a copolymer containing polyurethane structure, siloxane flexible segment and polyether segment. Under the same conditions, 1,3-dioxolane monomer was used as a control and the same operation was performed.

[0053] (1) Infrared spectroscopy test Tests were conducted at 600–1800 cm⁻¹ on the 1,3-dioxolane monomer and the copolymer prepared in Example 1, respectively. -1 Interval Fourier transform infrared spectroscopy test, such as Figure 1 As shown, the crosslinking copolymerization behavior of the system is verified by comparing the evolution patterns of the absorption peaks in the two spectral bands. The specific analysis is as follows: The gray curve represents the infrared spectrum of the 1,3-dioxolane monomer: the characteristic absorption peaks of the ring CH bending vibration and the cyclic COC skeleton corresponding to the five-membered ring structure can be clearly observed.

[0054] The red spectral lines represent the infrared spectrum of the copolymer: the significant decrease in the intensity of the characteristic absorption peak of the 1,3-dioxolane five-membered ring indicates that the 1,3-dioxolane monomer underwent ring-opening polymerization, and the original five-membered ring skeleton broke. The spectral lines are at 1200 cm⁻¹. -1 Nearby new linear - (COC) n The characteristic absorption peaks of the polyether segments confirm that linear polyether segments are generated after the ring-opening of 1,3-dioxolane and are covalently integrated into the crosslinking network, rather than being simply physically blended and doped with the matrix resin.

[0055] The characteristic structural peaks of the silicone-based polyurethane acrylate matrix are fully preserved: the characteristic peaks of the Si-O-Si silicon-oxygen backbone stretching vibration and the characteristic absorption band of urethane (-NH-COO-) are clearly present in the spectrum, while the characteristic peaks of the double bonds at the acrylate end groups are significantly weakened, indicating that the structure of the siloxane segments and the polyurethane backbone is stable and not destroyed during the copolymerization process; the vinyl acrylate participates in the free radical crosslinking reaction to achieve covalent bonding between the silicone-modified polyurethane backbone and the ring-opening 1,3-dioxolane polyether segments.

[0056] The characteristic vibrational peaks of siloxane remained stable, and the characteristic peaks of polyurethane showed no signs of disappearing. At the same time, the characteristic peaks of linear polyether generated by the ring opening of 1,3-dioxolane appeared simultaneously. This comprehensive evidence confirms that the trimethoxysilylpropyl acrylate ethoxycarbamate monomer and 1,3-dioxolane underwent covalent cross-linking copolymerization, and a copolymer containing polyurethane structure, flexible siloxane segments, and polyether segments was successfully prepared.

[0057] (2) Nuclear magnetic resonance Figure 2 The ¹H NMR spectra of the monomers in Example 1 before polymerization (gray curve) and after polymerization (red curve) are shown below. By comparing the formation and attenuation changes of the absorption peaks in the two spectra, the covalent copolymerization and crosslinking behavior of the two monomers is confirmed. The specific analysis is as follows: The gray spectral lines represent the ¹H NMR spectrum before polymerization: characteristic double peaks of the 1,3-dioxolane five-membered ring (δ=3.77ppm, δ=4.75ppm) can be observed, corresponding to the hydrogen signal of the cyclic ether skeleton; the DOL ring characteristic absorption peak in the red spectral lines of the copolymer is significantly weakened, proving that the 1,3-dioxolane monomer has undergone ring-opening polymerization and the five-membered ring structure has broken.

[0058] The red spectral lines represent the ¹H NMR spectrum after polymerization: the spectral lines show newly formed linear-(COC) at δ=3.60 ppm and δ=4.63 ppm. n The characteristic absorption peaks of the polyether confirm that DOL ring-opening forms linear polyether segments and is covalently integrated into the crosslinking network, indicating no simple physical blending behavior. The -NH-COO- characteristic peak remains stable, δ=5.8–6.4 ppm. The intensity of the vinyl acrylate characteristic peak decreases significantly, indicating that the acrylic end double bonds participate in free radical crosslinking, achieving covalent bonding between the monosilane polyurethane backbone and the ring-opening DOL polyether segments. The above results indicate that trimethoxysilylpropyl acrylate ethoxycarbamate and 1,3-dioxolane crosslinked copolymerize to successfully prepare a copolymer containing polyurethane structure, siloxane segments, and polyether segments.

[0059] Example 2

[0060] The preparation method is the same as in Example 1, except that the fluorocyclophosphonitrile flame retardant additive is changed to dimethoxytetrafluorocyclotriphosphonitrile.

[0061] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 54.5% diethylene glycol dimethyl ether, 3% dimethoxytetrafluorocyclotriphosphazene, 0.5% AIBN, 2% trimethoxysilylpropyl acrylate ethoxycarbamate, and 25% 1,3-dioxolane.

[0062] Example 3

[0063] The preparation method is the same as in Example 1, except that the fluorocyclophosphonitrile flame retardant additive is changed to ethoxypentafluorocyclotriphosphonitrile.

[0064] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 54.5% diethylene glycol dimethyl ether, 3% ethoxypentafluorocyclotriphosphazene, 0.5% AIBN, 2% trimethoxysilylpropyl acrylate ethoxycarbamate, and 25% 1,3-dioxolane.

[0065] Example 4

[0066] The preparation method is the same as in Example 3, except that the siloxane-modified urethane monomer is replaced with diethylene glycol acrylate-N-(3-trimethoxysilylpropyl)urethane, with the following structural formula: .

[0067] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 54.5% diethylene glycol dimethyl ether, 3% ethoxypentafluorocyclotriphosphazene, 0.5% AIBN, 2% trimethoxysilylpropyl diethylene glycol acrylate carbamate, and 25% 1,3-dioxolane.

[0068] Example 5

[0069] The preparation method is the same as in Example 3, except that the siloxane-modified urethane monomer is replaced with triethylene glycol acrylate-N-(3-trimethoxysilylpropyl)urethane, with the following structural formula: .

[0070] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 54.5% diethylene glycol dimethyl ether, 3% ethoxypentafluorocyclotriphosphazene, 0.5% AIBN, 2% trimethoxysilylpropyltriethylene glycol acrylate carbamate, and 25% 1,3-dioxolane.

[0071] Comparative Example 1 A liquid electrolyte is used, in which the solvent is diethylene glycol dimethyl ether, the sodium salt is NaPF6, and the concentration is 1 mol / L.

[0072] Comparative Example 2 The preparation method is the same as in Example 3, except that the polymerizable monomer is replaced with unmodified propylcarbamate diethylene glycol acrylate, with the following structural formula:

[0073] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 54.5% diethylene glycol dimethyl ether, 3% ethoxypentafluorocyclotriphosphazene, 0.5% AIBN, 2% diethylene glycol acrylate propylcarbamate, and 25% 1,3-dioxolane.

[0074] Comparative Example 3 The preparation method is the same as in Example 3, except that the polymerizable monomer is replaced with trimethoxysilylpropyl acrylate, with the following structural formula: .

[0075] The mass fractions of each component in the polymer precursor solution are as follows: 15% NaPF6, 54.5% diethylene glycol dimethyl ether, 3% ethoxypentafluorocyclotriphosphazene, 0.5% AIBN, 2% trimethoxysilylpropyl acrylate, and 25% 1,3-dioxolane.

[0076] Application Examples

[0077] The polymer electrolytes (electrolytes) prepared in the aforementioned examples and comparative examples were applied to sodium-ion batteries without negative electrodes, and their electrochemical performance was tested respectively.

[0078] A negative electrode-less sodium-ion battery includes a positive electrode, a separator, a negative electrode current collector, and an electrolyte.

[0079] Positive electrode preparation: Carbon-coated sodium iron pyrophosphate, conductive carbon black SP, and PVDF binder are mixed in a mass ratio of 93:4:3. NMP is added and stirred to form a slurry. The slurry is coated onto aluminum foil, dried, rolled and compacted, and cut for later use.

[0080] Negative current collector: carbon-coated aluminum foil.

[0081] Separator: Alumina ceramic modified PP / PE composite separator.

[0082] Battery assembly: A bare cell is obtained by alternately stacking positive electrode sheets, separators, and negative electrode current collectors; the bare cell is ultrasonically welded with positive and negative electrode tabs and then encapsulated with aluminum-plastic film to complete the top and side sealing pre-encapsulation; polymer precursor liquid is injected into the glove box and vacuum sealed; the encapsulated cell is placed in an oven and kept at a constant temperature of 60°C for 12 hours to complete in-situ crosslinking polymerization; after polymerization, it is cooled to room temperature and then subjected to cold and hot pressing for shaping, first charge and discharge formation, OCV static sorting, and capacity gradient detection to obtain a 1 Ah negative electrode-free quasi-solid-state sodium battery.

[0083] Note: If the liquid electrolyte of Comparative Example 1 is used, the electrolyte can be directly injected into the dry cell without the need for in-situ crosslinking polymerization.

[0084] Performance testing: (1) Cyclic performance test Room temperature cycling performance test: At 25℃, the negative electrode-free sodium-ion battery was charged to 3.6V at a constant current of 0.1C, and then discharged to 2.0V at a constant current of 0.1C. After activation twice, it was continuously cycled for 1000 cycles at a charge / discharge rate of 0.5C and a discharge rate of 1C. The capacity retention rate was calculated. High-temperature cycle performance test: After the battery is activated twice by 0.1C charge and discharge at 60℃, it is cycled 300 times at a charge / discharge rate of 0.5C and a discharge rate of 1C, and the capacity retention rate is calculated. The formula for calculating capacity retention rate is: Capacity retention rate = (Discharge capacity in the corresponding number of cycles / Discharge capacity in the first cycle) × 100%.

[0085] (2) High-temperature storage performance test A fully charged battery (100% SOC) was placed in a 60℃ constant temperature chamber for 28 days. After being removed, it was left to stand at room temperature for 10 hours and then discharged to 2.0V at a current of 0.1C. The high-temperature storage capacity retention rate was calculated. Capacity retention rate = (discharge capacity after high temperature storage / initial full charge capacity) × 100%.

[0086] (3) Thermal safety performance test ARC adiabatic accelerated calorimetry test: A fully charged battery is placed in an adiabatic accelerated calorimeter and heated from room temperature to 300°C at a rate of 5°C / min. The cell thermal runaway trigger temperature and peak temperature rise rate are recorded. Standard needle penetration safety test: With the battery fully charged, a steel needle with a diameter of 3mm is used to penetrate the cell at a constant speed perpendicular to the electrode plane. The temperature rise, fire, explosion and continuous heat release of the cell during the needle penetration process are recorded.

[0087] (4) Ionic conductivity test The bulk resistance of the battery at 25℃ and 60℃ was tested using the electrochemical impedance spectroscopy (EIS) method, and the ionic conductivity was calculated. The test frequency range was 10 Hz. -2 -10 6 Hz, AC amplitude 5mV.

[0088] The test results are shown in Table 1: Table 1 .

[0089] The test results in Table 1 show that: (1) Examples 1-5, which all use siloxane-modified urethane monomers and fluorocyclophosphonitrile flame retardant additives, are superior to the three comparative examples in terms of room temperature cycling, high temperature cycling, high temperature storage and thermal safety performance. The capacity retention rate is as high as 88.6% after 300 cycles at 60℃ and as high as 95.0% after 28 days of storage at 60℃. The ARC thermal runaway trigger temperature is 58℃ higher than that of traditional liquid electrolytes. There is no fire or explosion in the needle penetration test, which completely solves the pain points of traditional electrolytes such as rapid high temperature decay and large thermal safety hazards.

[0090] (2) The siloxane-modified urethane monomer is the core of performance: Comparative Example 2 has no siloxane structure and cannot construct a reduction-resistant hybrid SEI film. Its high-temperature cycling capacity retention rate is only 45.8%, which is much lower than that of the Example group; Comparative Example 3 has no urethane coordination structure, so its sodium ion transport capacity decreases and its high-temperature performance is also significantly weaker than that of the Example. (3) Fluorinated cyclophosphonitrile additives are key to high-temperature safety: The ethoxypentafluorocyclotriphosphonitrile used in Examples 3-5 has the best film-forming and flame-retardant effects, and its high-temperature cycling, storage and thermal safety performance are the best in the whole. (4) Polyether segment length adaptability: Examples 4 and 5 use longer diethylene glycol / triethylene glycol segment siloxane monomers. The flexible segments further reduce the interfacial impedance, and the ionic conductivity and cycle performance are improved simultaneously, making them more suitable for wide temperature range conditions.

[0091] (5) Comparative Example 1 uses traditional liquid electrolyte, which has no cross-linked network to bind the solvent and no flame retardant components. At high temperature, the solvent decomposes in large quantities to produce gas, the capacity decays very quickly, the thermal runaway temperature is the lowest, and the needle puncture directly ignites. The safety performance cannot meet the requirements of high safety scenarios at all. (6) Comparative Examples 2 and 3 retain only a single functional structure, which cannot achieve the synergistic effect of reduction-resistant framework, ion transport channel and flame-retardant film formation. Both high-temperature performance and safety performance have obvious shortcomings, which verifies the necessity of the multi-component synergistic design of this application.

[0092] Summarize: The high-safety polymer electrolyte and anode-free sodium-ion battery prepared in this application can achieve a capacity retention rate of up to 93.8% after 1000 cycles at room temperature (25°C), up to 88.6% after 300 cycles at 60°C, and up to 95.0% after 28 days of storage at 60°C. The thermal runaway trigger temperature in the ARC adiabatic test is increased by up to 58°C, and there is no risk of fire, explosion, or continuous heat release in the nail penetration test. At the same time, it has excellent ion conduction capabilities at both room temperature and high temperature, and takes into account long cycle life, high temperature stability, and high safety characteristics. It can be adapted to the application scenarios of anode-free sodium-ion batteries with high temperature and high safety requirements such as energy storage and low-speed transportation, and has extremely high industrialization and promotion value.

[0093] The exemplary embodiments of this application have been described above. However, the scope of protection of this application is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A method for preparing a high-safety polymer electrolyte, characterized in that... This includes the following steps: (1) Preparation of polymer precursor liquid Sodium salt, plasticizer, fluorocyclophosphonitrile flame retardant additive, initiator, siloxane-modified urethane monomer, and cyclic ether monomer are mixed to prepare a polymer precursor liquid. The fluorocyclophosphinitrogen flame retardant additive is selected from at least one of diethoxytetrafluorocyclotriphosphinitrogen, ethoxy-phenoxytetrafluorocyclotriphosphinitrogen, dimethoxytetrafluorocyclotriphosphinitrogen, bistrifluoroethoxytetrafluorocyclotriphosphinitrogen, ethoxypentafluorocyclotriphosphinitrogen, methoxypentafluorocyclotriphosphinitrogen, propoxypentafluorocyclotriphosphinitrogen, isopropoxypentafluorocyclotriphosphinitrogen, butoxypentafluorocyclotriphosphinitrogen, trifluoroethoxypentafluorocyclotriphosphinitrogen, phenoxypentafluorocyclotriphosphinitrogen, trimethylsiloxypentafluorocyclotriphosphinitrogen, and triethoxypentafluorocyclotriphosphinitrogen. Based on the total mass of the polymer precursor liquid, the mass fraction of the fluorocyclophosphinitrogen flame retardant additive is 0.5%-10%. The cyclic ether monomer is selected from at least one of 1,3-dioxolane, 1,3,5-trioxane, tetrahydrofuran, oxetane, 3-methyloxetane, 3-ethyloxetane, 1,4-dioxane monovinyl ether, and tetrahydrofuran-3-vinyl ether; the mass fraction of the cyclic ether monomer is 10%-50% based on the total mass of the polymer precursor liquid; The structural formula of the siloxane-modified carbamate monomer is as follows: ; Where: n≥1; Based on the total mass of the polymer precursor liquid, the mass fraction of the siloxane-modified urethane monomer is 1%-25%; (2) Preparation of high-safety polymer electrolytes The polymer precursor liquid is polymerized in situ at 40-90°C for 1-24 hours to obtain a high-safety polymer electrolyte.

2. The method for preparing a high-safety polymer electrolyte according to claim 1, characterized in that: In step (1): the sodium salt is at least one of NaPF6, NaClO4, NaBF4, NaBOB, NaODFB, NaCF3SO3, Na(CF3SO2)3, Na(CF3CO2)2N, Na(CF3SO2)2N, Na(SO2C2F5)2N and Na(SO3CF3)2N, and the mass fraction of the sodium salt is 12%-25% based on the total mass of the polymer precursor liquid.

3. The method for preparing a high-safety polymer electrolyte according to claim 1, characterized in that: In step (1): the plasticizer is selected from at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, acetonitrile, fluoroacetonitrile, isobutyronitrile, fluorobenzene, anisole, and methoxycyclopentane, and the mass fraction of the plasticizer is 20%-70% based on the total mass of the polymer precursor liquid.

4. The method for preparing a high-safety polymer electrolyte according to claim 1, characterized in that: In step (1): the initiator is selected from any one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, aluminum tri(trifluorosulfonate), aluminum bis(fluorosulfonyl)imide, tin trifluorosulfonate, magnesium bis(trifluoromethylsulfonyl)imide, indium trifluorosulfonate, magnesium hexafluoroantimonate, tri(pentafluorophenyl)borane, and zinc tetrafluoroborate. Based on the total mass of the polymer precursor liquid, the mass fraction of the initiator is 0.01%-5%.

5. The method for preparing a high-safety polymer electrolyte according to claim 1, characterized in that: In step (2): the polymerization temperature is 55-65℃ and the polymerization time is 2-12h.

6. A highly safe polymer electrolyte prepared by the method of claim 1.

7. The application of the high-safety polymer electrolyte of claim 6 in a negative electrode-free sodium-ion battery.